Mainstream Economics and Conventional Environmental Policies. Issue 3 (8th September 2022) - Obeng‐Odoom, Franklin
ABSTRACT: Is mainstream economics only about growth, efficiency, and sustainability? Many critics contend so, but the recent state of the art in economics suggests not. Respectively drawing on reformist neoclassical economics, neoclassical microeconomics "proper, " and behavioral economics, major studies show that mainstream economics provides theories of inequality and unsustainability. However, the theories of causation utilized remain largely neoclassical. Similarly, the bases for repairing the harms are grounded in neoclassical reasoning, while the mechanisms for restoration—ranging from minimalist interventions and income and substitution effects to behavioral nudges—are still mainstream. Fundamentally, they say little or nothing substantial about ecological imperialism, at the heart of which are rent theft and ecological debt, two critical cornerstones of world ecological crises. Therefore, mainstream economists certainly have, use, and apply theories of inequality and unsustainability, but mainstream economists neither have, use, nor apply transformative theories of social stratification, nor ecological imperialism generally. The overall effect of this disconnect from real‐world ecological crises is not simply that conventional environmental policies are incomplete, but that mainstream economics and conventional policies deflect attention from ecological imperialism behind veils of rhetoric, prices, and behaviors.